Two-dimensional multimetallic alloy nanocrystals: recent progress and challenges. Issue 37 (15th September 2021) - Zheng, Yiqun; Wang, Xiping; Kong, Yuhan; Ma, Yanyun
Abstract : In this highlight article, the recent progress on the preparation and application of multimetallic alloy nanocrystals with 2D nanostructures is systematically reviewed, as well as perspectives on future challenges and opportunities. Abstract : Multimetallic alloy nanocrystals (MMANCs) have attracted enormous research interest recently due to their ability to couple multiple metallic components confined in one particle body for potential synergetic effects of great interest. Among the typical structures, the two-dimensional (2D) architecture exhibits advantages in terms of a large surface area and aspect ratio, as well as unique crystal structure and tunable surface morphology. In this highlight article, we will systematically review the recent progress on the preparation and application of MMANCs with 2D nanostructures. This article will start with a brief introduction of 2D MMANCs, including their unique stacking-fault-involving crystal structures and typical strategies for preparation and characterization. In the next part, case studies categorized according to the synthetic methodology ( i.e., one-pot co-reduction, seed-mediated growth, galvanic replacement reaction, templated synthesis, etc. ) will be provided to illustrate the recent progress in this field. Finally, the electrocatalysis and plasmonics-related applications towards the as-mentioned 2D MMANCs will be discussed, as well as perspectives on the challenges and opportunities.